Identification of new aromatic cytokinins in Arabidopsis thaliana and Populus x canadensis leaves by LC-(+)ESI-MS and capillary liquid chromatography/frit-fast atom bombardment mass spectrometry - Tarkowská, Danuse; Dolezal, Karel; Tarkowski, Petr; Astot, Crister; Holub, Jan; Fuksová, Kvetoslava; Schmülling, Thomas; Sandberg, Göran; Strnad, Miroslav (Physiologia plantarum, 2003)
A search for naturally occurring aromatic cytokinins (ARCKs) in Arabidopsis thaliana plants and Populus x canadensis leaves led to the discovery of four new plant hormone substances: 6-(2-methoxybenzylamino)purine (ortho-methoxytopolin, MeoT), 6-(3-methoxybenzylamino)purine (meta-methoxytopolin, MemT) (Fig. 1) and their 9-beta-D-ribofuranosyl derivatives. These substances were identified by liquid chromatography electrospray ionization mass spectrometry [LC (+)ESI-MS] and capillary-liquid chromatography/frit-fast atom bombardment-mass spectrometry [CapLC/frit-FAB-MS] after pre-column derivatization. The chemical structures were subsequently confirmed by chemical synthesis. Because of lack of heavy labelled internal standards, the endogenous levels of methoxytopolins in A. thaliana plants, Populus x canadensis leaves and samples derived from cultures of Agrobacterium tumefaciens strain GV3101 were determined by enzyme-linked immunosorbent assay (ELISA) of HPLC-fractionated extracts. While the levels of MeoT, MemT and their ribosides in A. thaliana shoots and Populus x canadensis leaves were relatively low (approximately 0.25-10 pmol g-1 FW for MeoT and MemT, respectively), the A. tumefaciens strain produced up to 600 times more of the newly identified substances. Cytokinin activity of methoxytopolines was demonstrated in three bioassays testing their ability to stimulate tobacco callus growth, to delay chlorophyll degradation in excised wheat leaves, and to induce betacyanin synthesis in Amaranthus caudatus var. atropurpurea cotyledons. Notably, their anti-senescing activity in the wheat leaf assay exceeded that of BAP and Z by almost 200%. Methoxytopolins are proposed to be new members of the biologically active aromatic cytokinin family, which might have specific physiological functions.